2010
DOI: 10.1103/physrevlett.105.110401
|View full text |Cite
|
Sign up to set email alerts
|

Phases of a Two-Dimensional Bose Gas in an Optical Lattice

Abstract: Ultracold atoms in optical lattices realize simple condensed matter models. We create an ensemble of ≈60 harmonically trapped 2D Bose-Hubbard systems from a 87Rb Bose-Einstein condensate in an optical lattice and use a magnetic resonance imaging approach to select a few 2D systems for study, thereby eliminating ensemble averaging. Our identification of the transition from superfluid to Mott insulator, as a function of both atom density and lattice depth, is in excellent agreement with a universal state diagram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 24 publications
3
68
0
Order By: Relevance
“…It was shown that violation of the local-density approximation is a good indication of the critical behavior, which can be observed from the measurements of in situ density profiles and quasi-momentum distribution [348]. Experiments in two-dimensional lattices confirm this prediction and the critical values of J/U extracted from the measurements of the fraction of particles with zero momentum are consistent with QMC calculations for trapped systems [23].…”
Section: Criticality In Confined Systemssupporting
confidence: 61%
See 2 more Smart Citations
“…It was shown that violation of the local-density approximation is a good indication of the critical behavior, which can be observed from the measurements of in situ density profiles and quasi-momentum distribution [348]. Experiments in two-dimensional lattices confirm this prediction and the critical values of J/U extracted from the measurements of the fraction of particles with zero momentum are consistent with QMC calculations for trapped systems [23].…”
Section: Criticality In Confined Systemssupporting
confidence: 61%
“…For n = 1, the transition is always second order. First-order transition is possible for n ≥ 2 and U a /U s smaller than some critical value, which is about 0.188 for even n and grows from 0.012 (n = 3) to 0.015 (n → ∞) for odd n. In the case of 23 Na shown in Fig. 65, an interesting regime is achieved, when the QPT for odd n is second order, but for even n it is first order.…”
Section: First-and Second-order Phase Transitionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering more realistic cases, like the systems of 133 Cs or 87 Rb in an optical lattice [27,29], one can fix the tunnelling rate, J, and expect to see different regime in space by using local density approximation, i.e. the local chemical potential changes due to the inhomogeneous harmonic trap [34].…”
Section: Figmentioning
confidence: 99%
“…Taking interacting Bose gases as examples, thermal fluctuations in low dimensional system may lead to interesting topological excitations and the BerezinskiiKosterlitz-Thouless transition in two-dimensional systems [8,[20][21][22][23][24], which has been realized in current experiments [25][26][27]. When loading into an optical lattice, interacting bosons may undergo a superfluid (SF) to Mott insulator (MI) transitions [28,29] as predicted from a single band Bose-Hubbard model [30].…”
Section: Introductionmentioning
confidence: 99%